The Influence of Perceived Cultural and Business Distance on International Marketing Strategy Decisions; A Case study of Telkom Indonesia International - Hapsari, Carla; Stoffers, Jol; Gunawan, Agus (International Review of Management and Marketing, 2017)
World globalisation drives companies to undertake international expansion with the aim of retaining or growing their businesses. When companies globalize, managers encounter new challenges in making international marketing strategy (IMS) decisions, which are influenced by perceived cultural and business distance between their home- and foreign country. Telkom Indonesia International (Telin) was formed by Telkom Indonesia (i.e., the state-owned company in the telecommunication industry in Indonesia) to engage in international business within a global market. The central question in this study is to what extent do managers' perceived cultural and business distance between home- and foreign country influence their international marketing strategy (IMS) decisions? A mixed research strategy will be employed by applying qualitative and quantitative methods concurrently. The data collection will involve interviews with CEOs and managers, alongside a web survey to 55 managers of Telin. Results suggest important consequences for international marketing strategy decisions and emphasizes the need for dialogue on perceptions of cultural and business characteristics of countries. Keywords: Perceived Cultural and Business Distance; International Marketing Strategy; Strategy Decisions JEL Classifications: L1, M31